Pengembangan E-Modul Larutan Penyangga Berbasis Problem Based Learning Terintegrasi Etnokimia Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Nadia; Desy Kurniawati; Alizar; Budhi Oktavia (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to produce an electronic module (E-module) of buffer solutions based on ethnochemistry-integrated problem-based learning to improve students' critical thinking skills and analyze the level of validity, practicality, and effectiveness of the E-module on students' critical thinking skills. This type of research is Research and Development (R&D) with a 4-D development model. The 4-D development model consists of 4 stages of development, namely define, design, develop and disseminate. The results of the construct and content validity tests were 0.88, respectively, in the valid category. The results of the teacher and student practicality tests were 88.33% and 84.93%, respectively, in the very practical category. The N-Gain value analysis in the experimental and control classes was 0.71 and 0.46, respectively, in the high and medium criteria. The t-test results showed that students' critical thinking skills at SMAN 1 Bungo who used the E-module of buffer solutions based on ethnochemistry-integrated Problem-Based Learning were significantly higher than the control class that did not use the E-module. Thus, it can be said that the E-module on buffer solution material is valid, practical, and effective in significantly improving students' critical thinking skills.